Addicted to PBS? CBT can fix that: commentary on improving the adoption of PBS and ABA using diffusion of innovations. Issue 4 (1st October 2018) - Mason, Jonathan
Abstract : Purpose: The purpose of this paper is to provide a commentary to Hayward, Poed and McKay-Brown's article by expanding upon some of the reasons for the apparent dominance of Positive Behaviour Support (PBS). Design/methodology/approach: The commentary notes the rise and dominance of Cognitive behaviour therapy (CBT) over a similar time frame, and uses both this and ideas from the literature to examine the reasons for, advantages and consequences of PBS's dominance. Findings: The paper identifies three overlapping reasons for the comparable rise of PBS and CBT, and examines the impact that their dominance has had on attempts to manage quality, improve outcomes and train staff. Originality/value: Establishing the reasons for the success of a theoretical approach can assist with the development of other effective interventions.